A Global Degree Concept: Can It Fit into the Adventist Institutional Model of Higher Education? A Case Study - Gladstone, Ranjith Kingston (8ISC Abstract Proceedings, 2022)
Developing a Global Degree as a new educational structure and mode could address current inadequacies as countries and students confront new challenges. This new norm would help make learning more targeted, flexible, present, and applicable. Further, the Global Degree mission statement—is “one world, one degree, limitless capabilities.” On the other hand, White defines the aim of Adventist education as the harmonious development of all powers. This holistic education approach of Adventist higher education could accommodate the concept of limitless capabilities. This is a qualitative case study. This uses a single case study as a case analysis. The data is collected from Adventist educators from an international higher education institution. They can give a global perspective; hence they are the purposive sampling. After the ethics review board clearance, the data will be collected with permission from the gatekeepers. The data collected will be analyzed using Saldana’s framework. The themes will project the sense of the Adventist approach to the trending concept of global degree proposal. In addition, this study would brighten the vision of Adventist educators to prepare flexible learning platforms as part of an inclusive approach. Keywords : Global Degree, Qualitative Research, single case study, International higher education institution, Adventist Aim